Seismic response analysis of long-span continuous girder bridge considering fluctuating friction of bearing. (January 2023) - Liao, Man; Yang, Yongqing; Luo, Deng; Zhao, Canhui
Abstract: Under the combined action of horizontal and vertical earthquakes, separation-pounding of bridge beam ends and bearings occurs, which adversely affects the overall mechanical behaviour of any bridge. Based on D'Alembert's principle, this study proposes a theoretical analysis method to verify the separation of bridge beam ends and bearings, which is substantiated by the measured data. A three-span continuous steel-box-girder bridge was selected as the research object, and finite element models ( FEMs ) using the bilinear bearing and friction bearing models were established. The numerical models were verified by comparing the simulation results with the theoretical calculations. A comparative study on the seismic response of continuous girder bridges with different bearing models was conducted, and it was found that the friction bearing model is better for simulating the whiplash effect of long-span continuous girder bridges. The results indicate that the peak pounding force generated by the separation of the beam end and bearing is 1.74 times the weight of the beam end. Moreover, the whiplash effect causes the tension and compression stress states of the side span of the main beam to reverse and drastically reduce the compressive stress of the middle span by 70%. Finally, it is recommended that the friction bearing model which is able to realistically simulate the seismic response of the bridge more accurately be used to simulate bearings with large axial force fluctuations.